Earl Hooker, blues master - Danchin, Sebastian (American made music series., 2001)
The life and early death of a South Side guitar genius, the greatest unheralded Chicago blues-maker Jimi Hendrix called Earl Hooker "the master of the wah-wah pedal." Buddy Guy slept with one of Hooker's slides beneath his pillow hoping to tap some of the elder bluesman's power. And B.B. King has said repeatedly that, for his money, Hooker was the best guitar player he ever met. Tragically, Earl Hooker died of tuberculosis in 1970 when he was on the verge of international success just as the Blues Revival of the late sixties and early seventies was reaching full volume. Second cousin to n